I-Witness the best of Jay Taruc - Taruc, Jose Reyes III.; Flores, Marissa L.; GMA News and Public Affairs (Quezon City GMA Network, 2007)
"Panay De Motor" - Jay embarks on a motorcycle trip to document the urban legends of mystical Panay Island. "Maestrang Bulod" - A school in Sorsogon is so remote that teachers cannot go home everyday. They have to eat and sleep inside their classrooms. "Ako At Ang Butanding" - The mysterious arrival of whale sharks in Albay drives Jay into the waters, despite his decades-old fear of the open sea. "Gulong Ng Buhay" - Jay spends days in a wheelchair and discovers that the rights of persons with disabilities are almost completely ignored in Metro Manila. "Kapit Sa Patalim" - Small-time loggers in Quezon are torn between sustaining their natural resources and making a living.
Panay de motor (28 min.) -- Maestrang bulod (31 min.) -- Ako at ang butanding (27 min.) -- Gulong ng buhay (37 min.) -- Kapit sa patalim (34 min.)
Summay from container.
DVD.
Keywords: Demonology -- Philippines -- Panay; Folklore, Philippine; Endangered species -- Economic aspects -- Philippines -- Sorsogon; Wildlife conservation -- Economic aspects -- Philippines -- Sorsogon; Environmental policy -- Economic aspects -- Philippines -- Sorsogon; Whales -- Conservation -- Philippines -- Sorsogon; Physically handicapped -- Rehabilitation; Handicapped -- Services for; Loggers -- Philippines -- Quezon Province; Logging -- Law and legislation -- Philippines; Logging -- Philippines; Teachers -- Philippines -- Sorsogon; Rural schools -- Philippines; Social Problems -- Philippines; Health Services Needs and Demand -- Philippines; Poverty -- Philippines; Hunger -- Philippines; Philippines -- Social conditions